THE INVENTION RELATES TO A SYSTEM FOR COATING STEEL AGAINST ABRASIVE WEAR, WITH EASE OF INSTALLATION AND MAINTENANCE - ACTIS Fernando Augusto; BRUNA Roberto Gerardo (2025)
Competitive cost coating system for substrates subject to abrasive wear, comprising a plurality of abrasion-resistant steel plates having a predetermined shape and size to better engage protected, flat, or curved surfaces, such as vehicle cases for transporting minerals, hoppers, ducts, conveyor belts and similar equipment, used in various industrial fields, for example, in the transportation, mining, siderurgical, agricultural and building industries. The wear resistant plates are attached to the substrate to be protected by an adhesive with sufficient adhesion strength against tearing and shear, to hold the steel plates in place resisting impact and friction forces. The adhesive also facilitates replacement of such wear resistant steel plates by raising its temperature to reduce their adhesive strength. The adhesive is of the silane monocomponent type and the wear resistant plates are made of 15B30 steel, or of a steel of similar characteristics, with a hardness greater than 45 HRC Rockwell C after a tempering heat treatment, and preferably with a mainly martensitic microstructure and optionally carbonitriurate. Sistema de recubrimiento de costo competitivo para substratos sujetos a desgaste abrasivo, que comprende una pluralidad de placas de acero resistentes al desgaste por abrasión que tienen una predeterminada forma y tamaño para acoplarse mejor a las superficies protegidas, planas o curvas, tales como cajas o bateas de vehículos para transporte de minerales, tolvas, ductos, bandas transportadoras y equipos similares, utilizados en varios campos industriales, por ejemplo, en las industrias de transporte, minera, siderúrgica, agrícola y de construcción. Las placas resistentes al desgaste se unen al substrato que se va a proteger mediante un adhesivo con suficiente fuerza de adhesión contra el desgarramiento y al cizallamiento, para mantener las placas de acero en su lugar resistiendo las fuerzas de impacto y fricción. El adhesivo también facilita el reemplazo de dichas placas de acero resistentes al desgaste elevando su temperatura para reducir su fuerza adhesiva. El adhesivo es del tipo monocomponente de silano y las placas resistentes al desgaste están hechas de acero 15B30, o de un acero de características similares, con una dureza superior a 45 HRC Rockwell C después de un tratamiento térmico de templado, y preferiblemente con una microestructura principalmente martensítica y opcionalmente carbonitrurado.